Cebuano jocularity a Gricean interpretation - Lising, Jennifer Loy V. (2002)
Jokes published in magazines are some of the vehicles through which word play is used to achieve humor. This study aimed at finding out the nature of Cebuano jocularity and the way Cebuano jokes achieve humor through either observing or flouting the maxims in Grice's Cooperative Principle. A total of thirty jokes were analyzed in the study. The macro-structure followed by each was described and the humor was pointed out on the basis of how the entries observed or flouted the maxims. The results indicated that the majority of the entries followed the macro structure Introduction + Conversation. Moreover, it was found that most of the entries flouted the Maxim of Quality, the Maxim of Relation, and the Maxim of Manner.
Includes bibliographical references (page 103).